Presence of myocardial hypoenhancement on multidetector computed tomography after primary percutaneous coronary intervention in acute myocardial infarction predicts poor prognosis. (1st April 2015) - Ogasawara, Shinyu; Mukawa, Hiroaki; Sone, Takahito; Tsuboi, Hideyuki; Morishima, Itsuro; Uesugi, Michitaka; Matsushita, Etsushi; Morita, Yasuhiro; Okumura, Kenji; Murohara, Toyoaki
Abstract: Background: Recent research has suggested that patients with greater delayed contrast-enhanced size by multidetector computed tomography (MDCT) are more likely to experience adverse cardiac events and have poor prognoses over the long term. The myocardial hypoenhancement area in the delayed contrast-enhanced effect suggests microvascular obstruction. The outcomes of patients with a hypoenhancement area detected by MDCT have not been clear. We examined the clinical importance of myocardial hypoenhancement detected by delayed contrast-enhanced MDCT after percutaneous coronary intervention (PCI) in patients with acute myocardial infarction. Methods and results: In 80 patients with acute myocardial infarction, MDCT was performed immediately after primary PCI. We investigated the outcomes of the patients with hypoenhancement detected by MDCT. Myocardial hypoenhancement was observed in 14 patients (17.5%). All 14 of these patients with hypoenhancement had a transmural infarction, and their infarct volume was significantly higher than those of the patients without hypoenhancement (n = 66). During the median follow-up period of 309 days, the appearance of myocardial hypoenhancement was associated with the presence of slow flow/no-reflow, time from onset to reperfusion ≥ 6 h, aging, smoking, chronic kidney disease, and hyper-low-density lipoprotein cholesterolemia. The incidence of major adverse cardiovascular events (MACE) was significantly higher in the patients with hypoenhancement compared to those without hypoenhancement, regardless of the myocardial infarct volume. Conclusions: These results indicate that the presence of myocardial hypoenhancement in delayed contrast-enhanced MDCT after PCI as well as the extent of infarct area is an important predictor of MACE.